Keragaman Morfologi dan Molekuler Lasiodiplodia theobromae dari Tanaman Jeruk, Kakao, Karet, Manggis, dan Pisang - Fitri Kemala Sandra; Yayu Siti Nurhasanah; KIKIN MUTAQIN; Suryo Wiyono; Efi Toding Tondok (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2021)
Morphological and Molecular Diversity of Lasiodiplodia theobromae Isolated from Citrus, Cocoa, Rubber, Banana and Mangosteen Plants The fungus Lasiodiplodia theobromae is an important and cosmopolitan pathogen in the tropics and subtropics. The range of host plants is very wide, including economic commodities in Indonesia, i.e. citrus, cocoa, rubber, banana and mangosteen. The intraspecies diversity of fungi isolates from those five plants from different provinces in Indonesia was observed based on the morphological characteristics and molecular markers of RAPD-PCR. The intraspecies diversity was shown from the growth rate of the vegetative growth of the colonies on PDA as a base medium and the ability to produce reproductive structures. The fungal isolates from citrus, rubber and banana were able to grow faster and produce pycnidium and conidium in both PDA and modified-WA medium, while the cocoa and mangosteen isolates grow slower and only could produce these reproductive structures in the WA medium. The diversity between isolates in L. theobromae species was indicated by the morphological difference of the reproductive structures. Young conidium (aseptate) has a length ranging from 13.5-25.7 μm, width 8.1-14.0 μm, and length/width ratio 1.5-2.2; while for mature conidium (septate) 15.4-23.6 μm long, 10.7-12.8 μm wide, length/width ratio 1.4-1.9. Although the conidium sizes between isolates showed differences, they were still within the range of size of the L. theobromae species. The profile of RAPD-PCR DNA fragments using single primers OPB-01 and OPB-07 each resulted in different numbers and sizes of DNA bands between the five isolates, thus indicating the existence of molecular diversity between isolates within the same species.